ANALISIS KEPUASAN PELANGGAN TERHADAP PELAYANAN KERETA API BARANG PARCEL ONS DI STASIUN JAKARTA GUDANG.docx - Citra Ardhya Lestari; Winoto Hadi (LOGISTIK, 2018)
Transportation is one broad field. Transportation includes 3 (three) areas, land namely land, sea and air. goods delivery using land transportation can be done by one of them using train. When shipping of goods by train, it can be divided into containerized goods delivery and retail or Parcel Ounces. Jakarta Gudang Station serves Parcel Ons delivery, where there are 10 forwarders who came to the contract to ship goods using by train.PT. Kereta Api Indonesia (Persero) division of Cargo Transport is one of the companies that is engaged in providing a series for delivery of goods with a fleet of trains. Services provided will affect customer satisfactionwith the services we provide. If the customer is not satisfied with what we provide, the customer will not reuse our services. Of course there are obstacles that cause customers to feel dissatisfied. customer satisfaction level can bemeasured in various ways, one of which is a questionnaire. So far customers are satisfied with the services provided.